Silica Supported N-Heterocyclic Carbenes: Active and Reusable Heterogeneous Catalysts for Mizoroki-Heck Reactions - Açıkel, Müge; Artok, Levent (Izmir Institute of Technology, 2004)
Carbon-carbon bond formation reactions are among the most important processes in chemistry, as they represent key steps in the synthesis of more complex molecules from simple precursors. This thesis describes mainly the development of novel applications of the mild and versatile palladium-catalyzed carbon-carbon coupling method, commonly known as the Heck reaction. Most of the reactions performed in homogeneous media bearing the difficulty of separation from the reaction mixture. For this reason, N-heterocarbenes (NHCs) that gains scientific interest due to their high catalytic activity and stability were used to combine the practical advantage of a heterogeneous catalyst with the efficiency of a homogeneous system Immobilized Pd(NHC) complex 64 (A) and its modified derivatives (B and C),either with trimethylchlorosilane or with imidazolidinium salt 63, were synthesized. Characterization of the novel materials were performed using elemental analysis, AAS, NMR, DRIFTS and BET analysis. On the basis of the results, catalyst C showed higher activity among the others.The results also verified that the predominant activity of C could be ascribed to direct beneficial effect of imidazolidinium salt by being on the silica surface, in the vicinity of the anchored Pd-NHC complex 64. The catalyst showed high activity and reusability towards the Mizoroki-Heck reactions iodoanisole and bromoarenes (activated, nonactivated and deactivated) with styrene, when reactions at 140 °C in the presence of 1.5 molar equivalent NaOAc.3H2O base and 0.5 % Pd with respect to the aryl halide. The catalyst preserved its original activity for 4-iodoanisole, 4-bromoacetophenone, 4- bromotoluene and even for highly deactivated 4-bromoanisole reagent at least 7 uses.Although the addition of immobilized salt to the catalyst C increased the activity,addition of commonly used Bu4NBr showed no gradual increase in the activity. The catalyst C was also active for 4-chloroacetophenone albeit at higher temperature (170°C). The AAS analysis indicated that the reaction was truly heterogeneous.
Thesis (Master)--İzmir Institute of Technology, Chemistry, İzmir, 2004
Includes bibliographical references (leaves: 118-134)
Text in English; Abstract: Turkish and English
xii, 134 leaves
Keywords: QD505 .A18 2004; Heterogeneous catalysis; Heterocyclic compounds; Palladium catalysts